Spiritual dan Orientasi Wirausaha dalam Meningkatkan Penjualan: Studi pada Pelaku Usaha Fashion Muslim di Bencoolen Indah Mall Kota Bengkulu - Reza Anugrah Pratama; Khairiah Elwardah; Yenti Sumarni (Masyarakat Ekonomi Syariah Bogor, 2025)
The purpose of this study is to examine the influence of spirituality on increasing sales among muslim fashion entrepreneurs and the impact of entrepreneurial orientation on enhancing sales in Bencoolen Indah Mall (BIM), Bengkulu City. The research employs a qualitative approach, with data collection conducted through observation, interviews, and documentation. Data analysis is performed using the Miles and Huberman model. The findings indicate that spiritual values such as honesty, trustworthiness, responsibility, worship, and piety have a positive impact on business success. Entrepreneurial orientation, which includes innovation, adaptation to technology, risk-taking, proactivity, and customer focus, has proven effective in increasing sales. Muslim fashion entrepreneurs who can integrate spiritual values with a proactive entrepreneurial orientation tend to be more successful in facing challenges and achieving business objectives.